PEMBELAJARAN KONSERVASI DANAU SENTANI MELALUI CERITA PENCIPTAAN LANGIT DAN BUMI DI PAR GKI MARANATHA YOBOI, KABUPATEN JAYAPURA, PAPUA - Ohee, Henderite L.; Keiluhu, Henderina J.; Ngamelubun, Gerardinalia; Ohee, Lidia G.S.; Numberi, Vrinsye I.; Toruan, Alpredo D.A.L.; Siahaan, Andro Y.; Marani, Gilbert V.O.; Banundi, Zet (JURNAL PENGABDIAN PAPUA, 2024)
Lake Sentani is facing high pressure from various human activities that cause habitat degradation, so it has undergone significant changes in the last 20 years. The knowledge about Lake Sentani has also changed for the younger generation since the habitat alteration and degrataion and its biota have occurred. It can affect the younger awereness on Lake Sentani conservation. Therefore, in the community service, Sunday school children of GKI Maranatha Yoboi was learning on conservation of Lake Sentani through the story of the Creation of Heaven and Earth, to increased children's concern for the conservation of Lake Sentani. The community service program was carried out for 11 months, February-December 2024 with the GKI Maranatha Yoboi Sunday School Children. The program was done by using story telling. The community service program was evaluated by story retelling by children and coloring activities where both were competed. The results of the community service were analyzed descriptively using tables and pictures. Storytelling and coloring are good methods to improve children's social and environment awereness. Keywords: Awereness; Children; Genesis; Jayapura; Yoboi